Zearalenone Exposure Enhanced the Expression of Tumorigenesis Genes in Donkey Granulosa Cells via the PTEN/PI3K/AKT Signaling Pathway - Zhang, Guo-Liang; Song, Jun-Lin; Ji, Chuan-Liang; Feng, Yu-Long; Yu, Jie; Nyachoti, Charles M.; Yang, Gong-She (Frontiers in Genetics, 2018)
Zearalenone (ZEA) is a natural contaminant present in food and feed products. It cause reproductive disorders in domestic animals. In China, donkeys have high economic value and are at a high risk of exposure to ZEA. However, no information is available on the effects of ZEA-induced toxicity in donkeys. We used RNA-seq analysis to investigate the biological effects of ZEA on donkey granulosa cells (GCs). ZEA was administered at the concentration of 10 or 30 μM to GCs after 72 h of in vitro culture. The expression of tumorigenesis-associated genes in donkey GCs was drastically altered by exposure to 10 μM ZEA. Exposure to 10 or 30 μM ZEA considerably decreased the mRNA expression levels of PTEN, TGFβ, ATM, and CDK2 genes in GCs. ZEA exposure increased the expression of PI3K and AKT genes. Immunofluorescence, RT-qPCR, and Western blot analyses verified the gene expression patterns of ZEA-exposed GCs. Our results collectively demonstrate that ZEA exerts deleterious effects on the induction of ovarian-cancer-related genes via the PTEN/PI3K/AKT signaling pathway in donkey GCs in vitro.